School-based interventions for struggling readers, K-8 - Ortlieb, Evan.; Cheek, Earl H. (Bingley, U.K. : Emerald, 2013)
The volume highlights best practices of literacy instruction for students who have difficulties in reading. From components of effective pedagogy to instruction for specific populations, this text offers an array of expert perspectives on how to engage, scaffold, and prepare students to meet the multimodal demands of schools today. Renowned authors promote the notion that with thoughtful literacy and purposeful approaches to reading instruction, all children have the ability to improve their reading proficiencies. Core literacy instruction targeting comprehension, fluency, vocabulary, and writing development among others is of particular focus while supplementary discussions of factors such as native language, diversity, inclusion, and learning disabilities fully characterize issues related to struggling readers for which evidence-based approaches are presented to foster lasting success. It conveys a current portrayal of issues and trends of school-based literacy practices appropriate for novice and experienced educators and researchers alike.
Introduction / Evan Ortlieb -- Embracing complexity : integrating reading, writing, and learning in Intervention Settings / Katherine K. Frankel, Elizabeth L. Jaeger, P. David Pearson -- Fostering proactive reading instruction within the content areas / Evan Ortlieb, Wolfram Verlaan, Earl H. Cheek -- Meet them where they are : engaging instruction for struggling readers / Barbara A. Marinak, Linda B. Gambrell -- Scaffolding childrens reading during guided reading in intervention programs / Lea M. McGee, Kathryn S. Nelson -- From struggling reader to digital reader and multimodal composer / Bridget Dalton, Robin Jocius -- Struggling readers go online : building an integrated, inquiry-based classroom curriculum / Bernadette Dwyer -- Reaching and teaching thoughtful literacy to readers who struggle : increasing motivation, engagement, and comprehension / Michael L. Shaw -- Mobile devices for struggling readers in the classroom / Barbara McClanahan, Anne Stojke -- Vocabulary instruction : struggling readers becoming word wizards / Peter J. Fisher ... [et al.] -- Overcoming obstacles to deep comprehension of text : a continuum of narrative comprehension / Mary Applegate, Anthony Applegate -- Diverse literacy learners : deficit versus productive pedagogies / Jennifer Rennie, Evan Ortlieb -- Creating inclusive spaces for struggling readers / Leigh A. Hall, Leslie D. Burns, Heather Taxis Greene -- Closing the gap : reaching urban middle school students / Mary Shea, Rosemary Murray -- The plight of the upper grade English learner : comprehending, not just decoding! Using big picture strategies to reveal key ideas in texts / Janice Pilgreen -- Research-based reading instruction for students with learning disabilities / Lisa V. McCulley, Colby Hall, Sharon Vaughn.
Keywords: Education -- Teaching Methods & Materials / Reading & Phonics; Education -- Teaching Methods & Materials -- General; Education -- Testing & Measurement; Literacy strategies; Educational strategies & policy; Literacy -- Study and teaching